Survival analysis following early surgical success in intermittent exotropia surgery - Lee, Joo Yeon (International Journal of Ophthalmology Press, 2014)
AIM: To assess the consecutive recurrence following early success of intermittent exotropia surgery and to determine the clinical factors that affect the survival. METHODS: One hundred and thirty-five patients who underwent intermittent exotropia surgery and experienced early surgical success [≤5 prism diopters (PD) esophoria (E) to ≤10 PD exophoria (X) on the postoperative sixth month] were enrolled in this study. Their consecutive survival on the postoperative first year, second year and third year and at the last visit of fourth year or more, and the factors that might affect their survival, were analyzed. The final surgical outcomes after the postoperative fourth year were also investigated by dividing the patients into the success group (≤5 PD E to ≤10 PD X) and the failure group (>5 PD esodeviation or >10 PD exodeviation) RESULTS: The survival rates from the Kaplan-Meier analysis were 97.78%, 92.89%, 83.70% and 50.49% on the postoperative first, second and third years and fourth year or more, respectively. None of the clinical factors was determined to have affected the survival. The amount of the exodrift was largest (2.29 PD) between the first year and the second year, and smallest (1.47 PD) between the fourth year and the last visit. Sixty-three patients had their final visit after the postoperative fourth year, and 29 of them were in the failure group. Twenty-five patients in the failure group had an intermittent exotropia (IXT) of <20 PD with good to fair distant fusion; two had an IXT of <20 PD with poor distant fusion; one had an IXT of ≥20 PD with fair distant fusion; and another had delayed-onset consecutive esotropia. The exodeviation on the postoperative sixth month was smaller in the success group than in the failure group (2.81 PD vs 5.86 PD, P=0.012). The reoperation rate for recurrent IXT was 3.7%. CONCLUSION: The survival rate steadily decreases with the exodrift, but the amount of the exodrift decreases with long-term follow-up. The final outcomes demonstrate favorable results via surgical success or small-angle IXT with good fusion in most of the patients. A smaller deviation on the postoperative sixth month is associated with long-term survival.